2016
DOI: 10.1111/jcmm.12785
|View full text |Cite
|
Sign up to set email alerts
|

Protein profile of basal prostate epithelial progenitor cells—stage‐specific embryonal antigen 4 expressing cells have enhanced regenerative potential in vivo

Abstract: The long‐term propagation of basal prostate progenitor cells ex vivo has been very difficult in the past. The development of novel methods to expand prostate progenitor cells in vitro allows determining their cell surface phenotype in greater detail. Mouse (Lin−Sca‐1+ CD49f+ Trop2high‐phenotype) and human (Lin− CD49f+ TROP2high) basal prostate progenitor cells were expanded in vitro. Human and mouse cells were screened using 242 anti‐human or 176 antimouse monoclonal antibodies recognizing the cell surface pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several investigators have shown that SSEA-4 plays an important role in malignant characteristics of PC, such as regenerative potential and the loss of epithelial phenotype [10, 21, 22]. However, no study has reported on the relationships between SSEA-4 expression in cancer cells and the clinicopathological features of PC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have shown that SSEA-4 plays an important role in malignant characteristics of PC, such as regenerative potential and the loss of epithelial phenotype [10, 21, 22]. However, no study has reported on the relationships between SSEA-4 expression in cancer cells and the clinicopathological features of PC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SSEA-4 is a wellknown specific marker for pluripotent stem cells and a useful marker for identifying CSCs (17). Moreover, SSEA-4 expression is associated with remodeling and renewal in a variety of malignant cells (18)(19)(20) and is reportedly correlated with regenerative potential and loss of the epithelial phenotype in PC cells (21,22). Therefore, we hypothesized that SSEA-4 may be a CSC marker in PC, and that its expression might be associated with hormonal therapy resistance in these patients.…”
mentioning
confidence: 99%
“…SSEA-4 (also known as sialyl-Gb5) plays an important role in prostate cancer development by affecting adhesion of cells to extracellular matrix ( Sivasubramaniyan et al, 2015 ) and facilitating precise recognition of basal epithelial stem cell/progenitor cell lineages ( Hofner et al, 2016 ). Disialosyl globopentaosylceramide (DSGb5) is expressed in benign prostate tissue but not in prostate cancer.…”
Section: Prostate and Ovarian Cancermentioning
confidence: 99%